“Dissociating Form and Meaning in Bilingual Creative Writing and Creative Translation Workshops” - Sara GREAVES; Marie-Laure SCHULTZE (E-REA)
This article considers the various ways in which the principle of a disjunction between form and meaning can be applied to creative language teaching, as practised in our bilingual creative writing and creative translation workshops. While traditionally, language teaching is much concerned with conforming to rules and norms, here we try to provide a space in which the onus is on enhancing a personal appropriation of language. To this end, our theoretical foundations (Bettelheim and Lafforgue’s approach to fairy-tales as an indirect mode of expression) are only partially presented, and students are provided with bare plots to be filled with their own fictions or meaning. These ‘plots’ are designed to allow a creative engagement with the dynamics inherent in language, between intimacy and anonymity, familiarity and otherness, and thus to explore questions of identity. Similarly, language can be dismantled and reassembled afresh, in an apparently paradoxical pedagogy based on breaking, rather than making, monolingual linguistic habits. This contradicts the doxa according to which learning the rules comes first, any creativity later, and which we are not the only ones to believe unfounded. The study of New Englishes is also revealing in this light, with creativity often being looked upon as error. Naturally some self-reflexive dislocating of form and meaning has to be undertaken by the teachers, who may wonder “who” they should be – teachers or readers of creative fiction – when faced with their students’ productions. Indeed, postcolonial criticism invites us to consider spelling and grammar mistakes not as errors only, but as factors of difference.